Advances in Solid-Phase Microextraction - Naccarato, Attilio; Tagarelli, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Analysis imposes substantial challenges, especially when dealing with analytes present at trace levels in complex matrices. Although modern instrumentation has simplified analyses and makes them more reliable, its use is only the last step of the whole analytical process. On the other hand, sample preparation still represents the bottleneck in many analytical methods and often requires the use of extensive protocols before instrumental analysis. Solid-phase microextraction (SPME) is a well-established sample-prep technique for simultaneous extraction and pre-concentration of compounds from a variety of matrices. Given its compliance with the principles of green analytical chemistry, as well as the simplicity, versatility, and availability of different formats, SPME addresses several challenges associated with the traditional sample preparation approaches and allows for a substantial streamlining of the analytical workflow. This book is the reprint of a Special Issue that includes six contributions provided by some of the world's leading research groups in the field and focuses on recent advances in solid-phase microextraction.